서울 여름철 내화성 블랙카본의 질량과 입경분포 분석 - 임세희(Saehee Lim); 강유정(Yujeong Kang); 이미혜(Meehye Lee); 유희정(Hee-Jung Yoo); 이상삼(Sang-Sam Lee); 이건호(Gun-Ho Lee) (한국대기환경학회지(국문), 2019)
Black carbon (BC), a primary aerosol emitted by the combustion of fossil fuel and biomass, is the subject of scientific attention as its impacts on atmospheric pollution, human health and climate change. In the present study, the refractory BC (rBC) measurement method using a single particle soot photometer (SP2, DMT) was validated by developing and optimizing a precise calibration system. We measured mass and number concentrations and size distributions of ambient rBC in Seoul during 2019 summer. The mean mass and number concentrations of rBC particles were 0.58±0.32 μg m-3 and 336±190 # cm-3, respectively. The maximum count diameter of rBC was always found at around 70~80 nm, close to the lower detection limit, and the mass median diameter (MMD) of rBC was 119±5 nm on average. The elemental carbon (EC) mass concentration measured using a thermal-optical method (TOT) was 35% higher than that of rBC, which was likely associated with the differences in measured size range, refractory properties, and measurement uncertainties between two methods. The results clearly indicate that rBC particles in Seoul during summer was highly subject to urban local vehicle emissions. KCI Citation Count: 0